1970
DOI: 10.1161/01.res.27.6.921
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Coronary Artery Compliance in the Dog

Abstract: The dynamic compliance of 21 coronary arteries from 17 dogs was determined in situ. Intramyocardial portion* were occluded with a mixture of 200(1 glass beads and liquid silicone. To simulate in vivo pressure-volume conditions, 0.1 ml of saline was injected in 150 to 240 msec at a rate of 30 pulses/min. Silicone casts of the vessels, made at 100 mm Hg distending pressure, were used as a reference volume. The results indicate that the dynamic compliance decreases as the initial distending pressure rises. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 10 publications
3
38
1
Order By: Relevance
“…6). Allowing for an inner diameter to wall thickness ratio of -8-10, this Einc estimate is slightly lower than that implied by the modulus of volume distensibility reported by Patel and Janicki (19), which in turn is lower than the Cv values reported by Douglas and Greenfield (18). Our representative Ein, is an order of magnitude lower than the Einc reported by Cox (23).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…6). Allowing for an inner diameter to wall thickness ratio of -8-10, this Einc estimate is slightly lower than that implied by the modulus of volume distensibility reported by Patel and Janicki (19), which in turn is lower than the Cv values reported by Douglas and Greenfield (18). Our representative Ein, is an order of magnitude lower than the Einc reported by Cox (23).…”
Section: Discussioncontrasting
confidence: 61%
“…The pulsatile change observed from diastole to systole in the coronary diameter phasic waveform averaged 9% of the mean diameter, a value higher than predicted from experiments in anesthetized preparations (18,19). Late in diastole there were downward deflections in the coronary diameter waveform coincident with atrial systole and isovolumic ventricular systole.…”
Section: Discussionmentioning
confidence: 59%
“…Douglas and Greenfield (1970) found the epicardial capacitance function to be large enough to account for normal systolic stroke flow, but not of sufficient magnitude to account for systolic stroke flow during vasodilation. Other investigators have found the epicardial vessels to be very compliant, two to three times that of similarly sized systemic arteries (Arts et al, 1979), suggesting potential capacitive effects.…”
Section: Discussionmentioning
confidence: 88%
“…Because the epicardial arteries function in part as capacitors (Douglas and Greenfield, 1970), the phasic flow pattern in an epicardial coronary artery may not accurately reflect the phasic pattern of myocardial perfusion. Eckstein and his colleagues, in 1962, theorized that capacitance of epicardial arteries may distort the actual myocardial perfusion in three ways: (1) the magnitude of retrograde flow during systole is concealed because blood expelled from the deep myocardial layers distends the vessels and is not measured; (2) the antegrade systolic flow that is measured is, in part, a capacitance flow that distends the epicardial arteries; and (3) the measured antegrade diastolic flow is less than the actual perfusion since the epicardial capacitor would be discharging at this time.…”
mentioning
confidence: 99%
“…Previous studies (4,12) have investigated the dynamic elastic properties of canine coronary artery. In the current study, the ratio of E dyn/Estat (4) is used to adjust the dependence of Young's modulus on frequency.…”
mentioning
confidence: 99%